2021
DOI: 10.1161/atvbaha.120.315565
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidases Are Required for Full Platelet Activation In Vitro and Thrombosis In Vivo but Dispensable for Plasma Coagulation and Hemostasis

Abstract: Objective: Using 3KO (triple NOX [NADPH oxidase] knockout) mice (ie, NOX1 −/− /NOX2 −/− /NOX4 −/− ), we aimed to clarify the role of this family of enzymes in the regulation of platelets in vitro and hemostasis in vivo. Approach and Results: 3KO mice displayed significantly reduced platelet superoxide radical generation, which was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…This finding could be vital in preventing atherothrombosis, given the success of aspirin as a major antiplatelet drug limiting the production and release of TxA 2 . PDIA1‐based platelet pharmacology warrants future studies, given that recent studies highlighted the role of Nox1 function in platelets 43,54,55 …”
Section: Discussionmentioning
confidence: 99%
“…This finding could be vital in preventing atherothrombosis, given the success of aspirin as a major antiplatelet drug limiting the production and release of TxA 2 . PDIA1‐based platelet pharmacology warrants future studies, given that recent studies highlighted the role of Nox1 function in platelets 43,54,55 …”
Section: Discussionmentioning
confidence: 99%
“…Initially, Nox-2 was shown to be relevant to collagen receptor (GPVI)-mediated responses and regulate thrombus formation in male mice [ 8 ]. This has been disputed by us [ 9 , 10 ] and others [ 11 , 12 ] that showed that Nox-1 is the relevant isotype in GPVI-mediated responses, whilst Nox-2 is dispensable for thrombus formation. Such discrepant result across groups may be due to sex disparities amongst studies, as the initial report of Delaney et al used male Nox-1-deficient mice [ 8 ], whilst we have used female mice, noting that the Nox-1 gene is on the X chromosome [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The signaling pathway activated by CD36 includes tyrosine kinase- and protein kinase C-dependent activation of NOX2 and generation of reactive oxygen species (ROS), ultimately counteracting the negative regulatory function of the cyclic nucleotides cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP). Recent studies from our laboratory highlighted the involvement of both NOX1 and NOX2 in the signaling of ox-LDL [ 17 ] and confirmed the negative modulation of the cyclic nucleotide pathways by NOXs [ 18 ]. In addition to enzymatic ROS sources, HG causes metabolic overload in platelet mitochondria, which results in the leakage of electrons from the respiration chain and the release of ROS [ 32 ].…”
Section: Platelet Hyperactivity In Diabetesmentioning
confidence: 84%
“…Work in our laboratory showed that platelets from DM patients with poor glycemic control express significantly higher levels of the pro-oxidant enzyme nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 1 (NOX1) ( Figure 1 ). NOXs have been described as important positive regulators of platelet activity [ 17 , 18 , 19 , 20 ]. In view of the pro-thrombotic role of platelet NOXs both in vitro and in vivo ( Figure 2 ), the upregulation of NOX1 in DM patients contributes significantly to platelet hyperresponsiveness.…”
Section: Platelet Hyperactivity In Diabetesmentioning
confidence: 99%